THE ROLE OF PRINCIPLES OF CRIMINAL LAW IN CRIMINAL LEGAL DOCTRINE - Lykhova, Sofia; Sysoieva, Victoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Review of the monograph by O.S. Oliynyk "Principles of criminal law: concept, system and meaning"